2016
DOI: 10.1016/j.surfrep.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition—Sequential self-limiting surface reactions for advanced catalyst “bottom-up” synthesis

Abstract: Catalyst synthesis with precise control over the structure of catalytic active sites at the atomic level is of essential importance for the scientific understanding of reaction mechanisms and for rational design of advanced catalysts with high performance. Such precise control is achievable using atomic layer deposition (ALD). ALD is similar to chemical vapor deposition (CVD), except that the deposition is split into a sequence of two self-limiting surface reactions between gaseous precursor molecules and a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
227
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(233 citation statements)
references
References 387 publications
(512 reference statements)
2
227
0
4
Order By: Relevance
“…Furthermore, since ALD is dominated by a self-limiting growth mechanism, lm thickness and composition can be precisely controlled even on large-area substrates, and its good step coverage with excellent lm conformity can be extremely benecial in various applications. [8][9][10] To exploit the advantages of these remarkable features of the ALD process, various oxide semiconductors, such as ZnO, [11][12][13] In-O, 14 In-Zn-O, 6 and ZnSn-O, 15 have been prepared by the ALD process for TFT applications. TFTs with ALD-grown ZnO channels have been extensively investigated during the early developmental stages of oxide TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since ALD is dominated by a self-limiting growth mechanism, lm thickness and composition can be precisely controlled even on large-area substrates, and its good step coverage with excellent lm conformity can be extremely benecial in various applications. [8][9][10] To exploit the advantages of these remarkable features of the ALD process, various oxide semiconductors, such as ZnO, [11][12][13] In-O, 14 In-Zn-O, 6 and ZnSn-O, 15 have been prepared by the ALD process for TFT applications. TFTs with ALD-grown ZnO channels have been extensively investigated during the early developmental stages of oxide TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to the low coordinated sites were more active to react with TTIP precursors than terrace sites and facets. In fact, the oxide growth behavior is also affected with the choice of precursors, Biener and coworkers reported that using TiCl 4 and H 2 O to grow TiO 2 films with 10 cycles on Au tended to form continuous and smooth coatings. 87 The continuous coating completely encapsulated the Au surfaces resulted in the rapid disappearing of activity in CO oxidation.…”
Section: B Selective Passivation Of Edge/low-coordinated Sitesmentioning
confidence: 99%
“…The reactivity of precursors is a key factor to influence the selective growth sequences and behaviors on metals. We recently reported a facet selective ALD method, 41 by which cerium oxide {tetrakis(2,2,6,6-tetramethyl-3,5-heptanedionato) cerium(IV) [Ce(thd) 4 ] and O 3 as precursors} had been utilized to form nanofences around Pt NPs (shown in Fig. 9).…”
Section: Facet Selective Decoration Via Aldmentioning
confidence: 99%
See 1 more Smart Citation
“…This behaviour can be induced by growing thick metallic layers on top of a support layer with a different lattice constant using, for example, repeated atomic layer deposition cycles [12], or by mechanically applying surface-parallel strain to the system [13]. This technology is established in the semiconductor and metal-oxide-semiconductor field [14] but is less well understood for purely metallic surfaces.…”
Section: Introductionmentioning
confidence: 99%